National Crime Victimization Survey, Concatenated File, (United States), 1992-2016: Revised Version ([Verlag nicht ermittelbar], 2019)
The National Crime Victimization Survey (NCVS), previously called the National Crime Survey (NCS), has been collecting data on personal and household victimization through an ongoing survey of a nationally-representative sample of residential addresses since 1973. The NCVS was designed with four primary objectives: (1) to develop detailed information about the victims and consequences of crime, (2) to estimate the number and types of crimes not reported to the police, (3) to provide uniform measures of selected types of crimes, and (4) to permit comparisons over time and types of areas. Beginning in 1992, the survey categorizes crimes as "personal" or "property." Personal crimes include rape and sexual assault, robbery, aggravated and simple assault, and purse-snatching/pocket-picking, while property crimes include burglary, theft, motor vehicle theft, and vandalism. Each respondent is asked a series of screen questions designed to determine whether she or he was victimized during the six-month period preceding the first day of the month of the interview. A "household respondent" is also asked to report on crimes against the household as a whole (e.g., burglary, motor vehicle theft). The data include type of crime, month, time, and location of the crime, relationship between victim and offender, characteristics of the offender, self-protective actions taken by the victim during the incident and results of those actions, consequences of the victimization, type of property lost, whether the crime was reported to police and reasons for reporting or not reporting, and offender use of weapons, drugs, and alcohol. Basic demographic information such as age, race, gender, and income is also collected to enable analysis of crime by various subpopulations. This dataset represents the revised concatenated version of the NCVS on a collection year basis for 1992-2016. A collection year contains records from interviews conducted in the 12 months of the given year. Under the collection year format, victimizations are counted in the year the interview is conducted, regardless of the year when the crime incident occurred. The 2016 National Crime Victimization Survey (NCVS) violent and property crime estimates were significantly higher than 2015, but it was not possible to determine the degree to which the change in rates resulted from the sample redesign rather than real changes in U.S. victimization levels. Therefore, the Bureau of Justice Statistics (BJS) examined the 2015 and 2016 victimization rates separately for new and continuing sample counties in the 2016 Criminal Victimization bulletin. The BJS requested that the U.S. Census Bureau create a 2016 revised file with outgoing county interviews from July-December 2015, continuing county interviews from January-June 2016, and all interviews (continuing and new counties) from July-December 2016. In other words, the outgoing 2015 cases replaced the new 2016 cases in the first half of 2016. The files in this study serve as a separate research file to allow data users to make comparisons between 2015, 2016, and 2017 NCVS estimates using a nationally representative sample. It provides a sample that still represents the entire country but does not have the inflated crime rates seen in the new counties in 2016. For additional information on the dataset, please see the documentation for the data from the most current year of the NCVS, ICPSR Study 37296.